Numerical Analysis of Wind-Induced Particle Adhesion on High-Voltage Insulators Using COMSOL Multiphysics - Gorgoz, Irem; Cebeci, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2025)
High-voltage insulators are exposed to surface contamination caused by airborne pollution particles under varying environmental conditions. The deposition of these particles forms a pollution layer, increasing surface leakage currents and reducing the insulator's electrical strength, which raises the risk of surface flashover. In this study, particle motion and contamination on insulators under wind influence were analyzed using numerical methods. Two-dimensional (2D) simulations were conducted in COMSOL Multiphysics. First, the airflow field around the insulator was solved using a turbulence model. Then, particle transport and surface interaction were examined. The time-dependent particle behavior was evaluated for different wind velocities and particle sizes. Particle adhesion rates and resulting contamination levels are presented in tables and graphs. The findings reveal how wind speed and particle size influence contamination formation, offering valuable insight into the surface deposition behavior of particles. © 2025 IEEE.
2025 16th International Conference on Electrical and Electronics Engineering, ELECO 2025 -- 27 November 2025 through 29 November 2025 -- Istanbul -- 220282
Keywords: Adhesion; Computation theory; Deposition; Insulator contamination; Leakage currents; Particle size; Particle size analysis; Wind; Environmental conditions; Exposed to; High voltage insulators; Multi-physics; Particle adhesion; Particle forms; Particles sizes; Pollution particles; Surface contaminations; Surface leakage currents; Numerical methods